Spatiotemporal Changes of Reference Evapotranspiration in Mongolia during 1980–2006 - Wenjun Yu; Tonghua Wu; Weizhen Wang; Ren Li; Tianye Wang; Yanhui Qin; Weihua Wang; Xiaofan Zhu (Advances in Meteorology)
Reference evapotranspiration (RET) plays an important role in the terrestrial hydrological cycle. Applying the Penman-Monteith method, the RET over Mongolia was estimated from 1980 to 2006. The changing trends and magnitude of RET were detected by the Mann-Kendall test and Theil-Sen’s slope methods. Meanwhile, aridity indices were estimated using two different indices. The impacts of meteorological variables on RET were assessed through sensitive analysis by comparing the resulting RETs from artificially disturbed meteorological variables. The results indicated that the RET for 16 stations in Mongolia showed an increasing trend, particularly in the center and south. The calculated RET was higher than precipitation, which means severe droughts in Mongolia. The spatial patterns of RET are significantly influenced by climatic conditions as well as characteristics of the underlying surface (e.g., elevation and vegetation). The mean annual RET decreased from the south to the north, owing to sparse vegetation in the south of Mongolia. The sensitivity analysis revealed that the changes of RET were strongly affected by air temperature and relative humidity.